Job Description as a Means of Personalization of Labor Function of an Employee - Aleksey Nikolaevich Peters (Сибирское юридическое обозрение, 2011)
The article deals with correlation of the employment functions and job description of the employee. The author elaborates on the concept of job description, contents of the job description, role of job description in the personalization of the employee's responsibilities.